The Cambridge encyclopedia of human evolution - Jones, Steve 1944-; Martin, R. D. (Robert D.) 1942-; Pilbeam, David R. (Cambridge reference book, 1992)
Introduction to human evolution with coverage ranging from genetics to demography and disease. Includes diagrams, maps, and photographs